Sosialisasi Upaya Menyeragamkan Pertunasan Bibit Bawang Putih (Allium sativum L.) di Kecamatan Bojong, Kabupaten Tegal - Syaiful Anwar; Sobir Sobir (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Garlic (Allium sativum L.) is one of horticulture plant for spices. Planting material is an important factor of garlic production but it has a problem such as tuber dormancy period that takes 4 months. There’s necessary to use some techniques to break the dormancy for the growth uniformity. This socialization is how important to uniforming the garlic seed growth. Participants were followed by garlic farmers in Tuwel and Rembul villages and field extension officers (PPL) in Bojong District. Several factor that affect the unformity of the seed growth are the dormancy hasn’t broken and low calcium (Ca) absorption. The storage (7 oC) for 2 months after harvesting can increase the emergence of shots (dormancy rupture) and increase the seed growth rate by 85,4%. Low Ca absorpstion can be resolved by appling calcite lime (CaCO3). Preparation of planting material can be done by soaking the garlic seeds overnight or by immersing the plant growth promoting rhizobacteria (PGPR) treatment for 10-15 minutes.